1998
DOI: 10.1239/jap/1032265214
|View full text |Cite
|
Sign up to set email alerts
|

A threshold limit theorem for the stochastic logistic epidemic

Abstract: The time until extinction for the closed SIS stochastic logistic epidemic model is investigated. We derive the asymptotic distribution for the extinction time as the population grows to infinity, under different initial conditions and for different values of the infection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
117
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(124 citation statements)
references
References 9 publications
6
117
1
Order By: Relevance
“…The S I S type dynamics (Anderson and May 1991) is considered on a network with N nodes and with adjacency matrix G = (g i j ) i, j=1,2,...,N ∈ {0, 1} N 2 where g i j = 1 if node i and j are connected, and g i j = 0 otherwise. Here, we only consider networks with bi-directional edges and without self-loops.…”
Section: Disease Dynamics and The Network Of Contactsmentioning
confidence: 99%
See 2 more Smart Citations
“…The S I S type dynamics (Anderson and May 1991) is considered on a network with N nodes and with adjacency matrix G = (g i j ) i, j=1,2,...,N ∈ {0, 1} N 2 where g i j = 1 if node i and j are connected, and g i j = 0 otherwise. Here, we only consider networks with bi-directional edges and without self-loops.…”
Section: Disease Dynamics and The Network Of Contactsmentioning
confidence: 99%
“…county etc), disease characteristics and various control programmes that are aimed at halting disease transmission or bringing infection prevalence to as low a level as possible (Anderson and May 1991). The main aim of many models is to gain insight into how diseases transmit and to identify the most effective strategies for their prevention and control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As for the stochastic logistic model, according to Na˚sell (2001) its study goes back to Feller (1939); however, approximations for the mean time to extinction have been determined only recently (Na˚sell, 1996;Andersson and Djehiche, 1998;Na˚sell, 2001;Ovaskainen, 2001). In particular, Na˚sell (2001) showed that the mean time to extinction starting from quasi-stationarity (that is, the distribution of local abundance conditional on non-extinction) increases exponentially with the carrying capacity K and scales as 1=r if the corresponding deterministic model corresponds to a viable population, namely if r ¼ nð0Þ À mð0Þ40.…”
Section: Persistence-extinction Boundaries In the Spatially Explicit mentioning
confidence: 99%
“…The stochastic logistic model provides a typical example. Under these simplifying assumptions, results have been obtained concerning the quasi-stationary distribution (Ovaskainen 2001), time to extinction of the metapopulation (Andersson and Djehiche 1998) and the limiting behaviour (Ethier and Kurtz 1986;Pollett 2001) which connects the stochastic logistic model to Levins's model (1969). More recently, researchers have tried to bring the modelling assumptions closer to the ecological reality.…”
Section: Introductionmentioning
confidence: 99%